Geocronologia por traço de fissão em apatitas de rochas alcalinas: comparação dos diferentes métodos de datação e calibração da dosimetria de nêutrons - Soares, Cleber José [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
External Detector Method is a widely used technique in Fission Track Thermochronology, FTT, in which two different minerals are concomitantly employed: spontaneous tracks are observed in apatite and the induced ones in the external detector muscovite. They show intrinsic differences in detection and etching properties that should be taken into account. In this work, new geometry factor values, g, in apatite were obtained by ρED/ρIS ratio and GQR values through the measurement of projected lengths. Five mounts, two of which were large area prismatic sections (Mn-1 and Mn-2, Durango apatite) and three samples composed of random orientation pieces (D-2 and D-3, Durango apatite and TF-42, from crystalline rock) have been used to determine the g-values. A side effect of applying EDM is that the value of the initial confined induced fission track, L0, is not measured in routine analyses. The L0-value is an important parameter to quantify with good confidence the degree of annealing of the fossil fission tracks in the unknown age sample, being essential for accurate thermal history modeling. The impact of using arbitrary L0- values on the inference sample thermal history was investigated and discussed. The L0- value can be measured for each sample as an extension of the ρED/ρIS ratio method for measuring g, which consists in simultaneously irradiating pre-annealed apatite grains and the EDM mount of the same sample. The ratio between densities of induced tracks in the muscovite and in the extra apatite mount gives the value of g. L0 is the mean length of the confined fission tracks measured in the extra apatite mount. Eight apatite samples from crystalline basement, with grains at random orientation, were used to determine the gvalues. The resultant average found (0.560.02) is statistically in agreement with the values found for... (Complete abstract click electronic access below)
Keywords: Datação do traço de fissão; Geologia estratigráfica; Termocronologia; Apatita; Tempo geológico; Rochas igneas alcalinas